Molecular and morphological systematics of soil-inhabiting Cryptorhynchinae of the genus Acallorneuma and the tribe Torneumatini (Coleoptera: Curculionidae), with description of two new species. - Stüben, Peter E.; Schütte, André; López, Heriberto; Astrin, Jonas J. (Contributions to Entomology = Beiträge zur Entomologie, 2016)
Starting from an ecological classification of the morphotypes of apterous western Palaearctic Cryptorhynchinae, molecular systematic and morphological results for the monophyletic weevil genus Acallorneuma Mainardi, 1906 and the tribe Torneumatini Bedel, 1884 are presented. Based on the mitochondrial CO1 barcoding region, we discuss the limits of comparative morphology in the uniform Acallorneuma species. A catalogue and a pictorial key of all 8 species of Acallorneuma are provided. In a second step we compare morphology-based systematics of the genus Acallorneuma with our molecular reconstruction. Finally, we focus on the related blind, equally wingless and uniform, currently 71 species of the tribe Torneumatini living deep in the soil. This overview of the present state of research shows that molecular intrageneric resolution is highly dependent on the number of sampled species, especially in those cases with particularly long edges in the dendrogram. But although Torneumatini sampling was not complete due to the elusiveness of these subterranean species, some taxonomic changes could still be implemented: Torneuma s. str. with the type species Torneuma caecum Wollaston, 1860 occurs only on the Madeira archipelago. The species of the subgenus Paratyphloporus Solari, 1937 stat. nov. - only from the western Canary Islands(!) - must be transferred into the genus subgenus Paratorneuma Roudier, 1956 stat. nov. For all other species of the Mediterranean area and the eastern Canary Islands, the systematic classification needs to be remade (incertae sedis, see also appendix 2). Torneuma deplanatum deplanatum (Hampe, 1864) is the type species of the subgenus Typhloporus that includes some, but not all Mediterranean species with a constantly deep and wide pectoral canal, which - as it now seems likely – was developed several times. Two new species are described: Torneuma (s. str.) isambertoi Stüben spec. nov. from Madeira and Torneuma (s.l.) cadizensis Stüben spec. nov. from the south of Spain. In both cases keys are given to differentiate from the closely related species.KeywordsAcallorneuma, Torneumatini, Torneuma, Bayesian analysis, Integrative Taxonomy, morphology, CO1, new species, taxonomic changes, Western Palaearctic, Spain, Portugal, Canary Islands, Madeira.Nomenclatural Actsisambertoi Stüben, 2016 (Torneuma (s. str.)), spec. nov.cadizensis Stüben, 2016 (Torneuma (s.l.)), spec. nov.